Strategies for prevention of soccer related injuries: a systematic review. Issue 1 (29th January 2004) - Olsen, L; Scanlan, A; MacKay, M; Babul, S; Reid, D; Clark, M; Raina, P
Abstract : Objectives: To examine evidence on the effectiveness of current injury prevention strategies in soccer, determine the applicability of the evidence to children and youth, and make recommendations on policy, programming, and future research. Methods: Standard systematic review methodology was modified and adopted for this review. Research questions and relevance criteria were developed a priori. Potentially relevant studies were located through electronic and hand searches. Articles were assessed for relevance and quality by two independent assessors, and the results of relevant articles were abstracted and synthesised. Results: A total of 44 potentially relevant articles from electronic (n = 37) and hand (n = 7) searches yielded four that met inclusion criteria. These four studies addressed a range of intervention strategies and varied with respect to results and quality of evidence. Conclusions: Some of the strategies look promising but lack adequate evaluation or require further research among younger players. Practice, policy, and research recommendations are provided as a result of the synthesis.